Blue Planet in Peril: The Global Health Crisis of Water Pollution - Sharangouda J. Patil; Vijaylaxmi C; Sandeep V. Binorkar; Basavarajeshwari Indur; Vijayalaxmi Warad; Deekshitha, M. B; Rajeshwar V; Praveen kumar Kalva; Vishwanatha T (The Bioscan, 2025)
Water is an essential resource for living organisms which covers 70 per cent of the Earth’s surface and is the foundation of life and health of the ecosystem. It supports all the living organisms to sustain in diverse habitats. Most of the water bodies such as oceans, rivers, lakes, ground water and aquifers are contaminated with industrial effluents which affect aquatic ecosystem and their habitat. Hence, water pollution is a major issue of environment. It is the second most prevalent type of environmental pollution. Understanding the reasons, causes and effects of water pollution is therefore crucial for preserving our planet’s most valuable resource.